2021
DOI: 10.1063/5.0071763
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapping in bismuth-based semiconductors: Opportunities and challenges from optoelectronic devices to quantum technologies

Abstract: Semiconductors based on bismuth halides have gained attention for a wide range of electronic applications, including photovoltaics, light-emitting diodes, and radiation detectors. Their appeal is due to their low toxicity, high environmental stability under ambient conditions, and easy processability by a wide range of scalable methods. The performance of Bi-based semiconductors is dictated by electron–phonon interactions, which limit carrier mobilities and can also influence optoelectronic performance, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 95 publications
2
33
0
Order By: Relevance
“…Moreover, we note that no initial structural perturbation was required to induce self-trapping (as is often required in simulations of polaronic trapping 46,47 ), indicating a negligible energy barrier to hole trapping and thus rapid charge-carrier localisation 25 . This behaviour is consistent with low electronic dimensionality in semiconductors 45,48 , and has been linked to similar ultrafast localisation in other bismuth-based materials 22,26 . While the closepacking of NaBiS 2 bestows high structural dimensionality, the effective electronic dimensionality of the band-edge states is vastly reduced due to the spectator nature of Na + and nanoscale heterogeneity in cation distribution.…”
Section: Mechanism For Charge-carrier Localisationsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, we note that no initial structural perturbation was required to induce self-trapping (as is often required in simulations of polaronic trapping 46,47 ), indicating a negligible energy barrier to hole trapping and thus rapid charge-carrier localisation 25 . This behaviour is consistent with low electronic dimensionality in semiconductors 45,48 , and has been linked to similar ultrafast localisation in other bismuth-based materials 22,26 . While the closepacking of NaBiS 2 bestows high structural dimensionality, the effective electronic dimensionality of the band-edge states is vastly reduced due to the spectator nature of Na + and nanoscale heterogeneity in cation distribution.…”
Section: Mechanism For Charge-carrier Localisationsupporting
confidence: 84%
“…2a, it can be seen that the weak anti-bonding character within the VB of disordered NaBiS 2 leads to a less disperse VBM and hence a hole effective mass of m h = 1.04 m 0 that is twice as heavy as that of AgBiS 2 (m h = 0.51 m 0 ), although the electron effective masses for both materials are similarly small (m e = 0.24 m 0 ), owing to their shared Bi p -S p derived CBM. The large dielectric constant and heavier effective masses in disordered NaBiS 2 thus yield intermediate Fröhlich electron-and hole-phonon coupling constants (α e OP and α h OP ) of 1.40 and 2.92, which are higher than AgBiS 2 (α e OP = 1.09, α h OP = 1.63) and comparable to double perovskites as well as methylammonium lead iodide perovskites (2-3) 25,45 . The hole-phonon coupling constant here was calculated using the hole effective mass in the 'bulk VBM' rather than the localised S p states arising at Na + -rich inhomogeneities, owing to the breakdown of the effective mass model for such highlylocalised states.…”
Section: Charge-carrier Kinetics In Nabis 2 Nanocrystal Filmsmentioning
confidence: 97%
“…The reduced carrier mobility associated with self-trapping in CABI 16 leads to low drift and diffusion lengths. 14 The suppressed self-trapping of the photoexcited carriers in the case of CABI-Sb results in a higher number of free excitons than in pristine CABI, leading to more effective charge separation and extraction, which, in turn, may enable an enhanced JSC and device performance in CABI-Sb photovoltaics. 14…”
Section: Suppressed Carrier Self-trapping In Cabi Through Sb Alloyingmentioning
confidence: 99%
“…10 The reasons for such modest efficiencies lie in the low open-circuit voltage (VOC) and short-circuit current density (JSC) values, mainly due to poor charge carrier transport resulting from abundant intrinsic defects and other typical recombination losses in this class of materials, such as self-trapping. 13,14 Despite being one of the most recently discovered pnictohalides, Cu2AgBiI6 (CABI) has already gained an exceptional interest from the photovoltaic and optoelectronic community owing to its direct bandgap, high absorption coefficient, low exciton binding energy, and the desired band gap of ≈ 2 eV for IPVs. 8,9,15,16,17,18 Several works have contributed to improving CABI discontinuous morphology, consisting of small-sized grains and numerous cracks, by passivating the surface defects (e.g., via hydroiodic acid additive incorporation, 8 phenethylammonium iodide treatment, 18 or film deposition engineering 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The most popular of these elpasolites for optoelectronics is Cs 2 AgBiBr 6 , which has been found to have long charge-carrier lifetimes exceeding 100 ns (in thin films), [6][7][8][9] although recent studies have suggested that this is due to the detrimental formation of small polarons. [10][11][12][13] Apart from questions around charge-carrier transport, an important limitation with Cs 2 AgBiBr 6 is that its bandgap (2.25 eV) [14] exceeds the optimal values for single-junction photovoltaics (PVs), indoor PVs, as well as top-cells for tandem PVs. [15][16][17][18][19] Partly because of the wide, indirect bandgap, attempts at fabricating single-junction PVs have yielded power conversion efficiencies (PCEs) up to only 4.23%, [20] with most reports <3%.…”
Section: Introductionmentioning
confidence: 99%